A Feasibility Study for An Integrated Approach to Fall Prevention in Community Care: Stay Up and Active in Orange County - Spencer Lindgren; Spencer Lindgren; Katie Kwaschyn; Ellen Roberts; Jan Busby-Whitehead; Lori Evarts; Tiffany Shubert (Frontiers Media S.A., 2016)
Introduction: Falls amongst persons over 60 present significant risks for serious injury or debility. Falls place burdens on Emergency Medical Services (EMS), hospitals, and the adults themselves. Recognizing a need to provide interventions to minimize risk, Orange County Emergency Services (OCES), the Orange County Department on Aging (OCDoA), and the University of North Carolina at Chapel Hill (UNC) partnered to create the Stay Up and Active Program (SUAA). Methods: A streamlined workflow algorithm between the OCES and OCDoA was created and employed to provide falls risk assessment and necessary services. Qualitative techniques were used to assess the need for such a program and its potential impact. A subset of individuals were interviewed three months after the intervention to assess the impact of the intervention on their fall risk. Results: In the first seven months, 478 instances of individuals who called OCES screened positive for falls risk. Of the 478 positive screenings, 55 individuals were identified as having received more than one positive fall screen due to multiple calls. The maximum number of positive screenings by one individual was 14. More women (61.3%) than men screened positive for fall risk. Individuals 88 years of age (6.9%) represented the mode of the individuals with positive screens. Nineteen (4.0%) people who called OCES and received the intervention completed a three month follow up survey. Of the nineteen, 86% (n=16) reported no recurrent fall.Conclusion: The number of individuals who screened positive supports the need for early identification and intervention through EMS. This program identified several challenges connecting older adults with services already available to keep them independent which provided insight to all stakeholders regarding factors that inhibit the program's success. The program evaluation should continue to provide suggestions for improvement and ensure sustainability.